2006
DOI: 10.1136/ip.2006.012872
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for reducing risky teen driving behaviors among minority youth: Figure 1

Abstract: Teenage drivers, especially males, have higher rates of motor vehicle crashes and engage in riskier driving behavior than adults. Motor vehicle deaths disproportionately impact youth from poor and minority communities and in many communities there are higher rates of risky behaviors among minority youth. In this paper, the authors review the data on teens, risky driving behaviors, and morbidity and mortality. They identify areas in which known disparities exist, and examine strategies for changing teen driving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 85 publications
0
26
0
Order By: Relevance
“…Little is known of what teenagers perceive as driving dangers, factors to enhance safety, or ways to present interventions that resonate with youths. 44,[47][48][49][50][51][52] To effectively influence teenaged drivers' safety, we must understand risk and safety from their viewpoint.…”
mentioning
confidence: 99%
“…Little is known of what teenagers perceive as driving dangers, factors to enhance safety, or ways to present interventions that resonate with youths. 44,[47][48][49][50][51][52] To effectively influence teenaged drivers' safety, we must understand risk and safety from their viewpoint.…”
mentioning
confidence: 99%
“…Juarez et al reported that multisectoral prevention strategies which are culturally appropriate and engage the target population are effective. 31 In the context of the Erbil community in Iraq, prevention strategies could include the implementation of educational and awareness programmes for medical students. These programmes would aim to reduce enjoyment of risky driving behaviours, improve risk perception and remind students to act as role models for safe driving behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…7,15,18 As more evidence-based DE programs are implemented and rigorously evaluated, attention should be paid to possible implications of underutilization by lower-income, male and minority teens, especially given that these groups are reported to have higher rates of risky driving behaviors and crashes. 19,20 Because …”
Section: Discussionmentioning
confidence: 99%